Effectiveness of STEM-Based Mind Mapping Learning Model to Improve Students' Science Literacy in the Era of Revolution 4.0 - Slamet Hariyadi; Agus Rofi’i; Tomi Apra Santosa; Taqiyuddin; Bayu Purbha Sakti (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to analyze the size effect of the STEM-based mind mapping learning model to increase students' scientific literacy in the revolutionary era 4.0. This type of research is meta-analysis. The research samples came from 15 national and international journals published from 2018-2023. The method for selecting this meta-analysis research data is through the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Search for data sources through Google Scholar, Wiley, Eric and ProQuest. Data source collection techniques are direct observation and documentation through online databases. Data analysis is a quantitative analysis by calculating the effect size, standard error and average value with the help of the JSAP application. The results showed that from this study it could be concluded that the combined effect size value was (d = 1.30; p < 0.05) high criteria. These findings explain that STEM-based mind mapping models are more effective in improving scientific literacy skills in the 4.0 revolution era than conventional learning models. The STEM-based mind mapping learning model provides a new breakthrough in the world of educational technology.